2015
DOI: 10.1155/2015/492782
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Is the Most Frequent Final Diagnosis of Focal Liver Lesions Identified in a Cross-Sectional Evaluation of Patients with Chronic Liver Disease in Saudi Arabia

Abstract: Background.Hepatocellular carcinoma (HCC) is a frequent diagnosis in patients with chronic liver disease (CLD) and a newly identified liver lesion, although benign diseases may also be responsible for this finding.Objective.To evaluate the characteristics of focal liver lesions in a population of patients with CLD not under surveillance for HCC in the Middle East.Methods.We performed a cross-sectional study evaluating 77 patients with CLD and a focal liver lesion identified during ultrasonography. Patients’ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Cancer rates are rising worldwide, and breast cancer is considered to be the second leading cause tumor-related deaths in women in Saudi Arabia 48 , with colon cancer being the third leading cause of death, and a high mortality rate observed for breast cancer worldwide 49 . Liver malignancy is another common diagnosis in middle-eastern patients who suffer from chronic liver disease 50 . The toxicity of the ASNase produced by B. licheniformis in this study was evaluated for cancer cell lines, the results of which showed that the enzyme was highly toxic toward HepG-2 cells, more so than against MCF-7 and HCT-116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer rates are rising worldwide, and breast cancer is considered to be the second leading cause tumor-related deaths in women in Saudi Arabia 48 , with colon cancer being the third leading cause of death, and a high mortality rate observed for breast cancer worldwide 49 . Liver malignancy is another common diagnosis in middle-eastern patients who suffer from chronic liver disease 50 . The toxicity of the ASNase produced by B. licheniformis in this study was evaluated for cancer cell lines, the results of which showed that the enzyme was highly toxic toward HepG-2 cells, more so than against MCF-7 and HCT-116 cells.…”
Section: Discussionmentioning
confidence: 99%